Through the eyes of engineers: writing in engineering contexts - Leydens, Jon A., author; Davies, Timothy Gray, advisor; Banning, James H., advisor; Kiefer, Kathleen E., committee member; Lile, Derek, committee member; McBride, William G., committee member (Colorado State University. Libraries, 2004)
This phenomenological study of writing gleaned understandings from participants about the role of writing in mining engineering workplace contexts and in a university-level project-based senior design (SD) capstone course in mining engineering. While secondary data came from SD classroom observations and course documents, the primary data emerged from interviews with four groups of participants, including SD instructors, students, clients, and alumni. Participants ranged from college seniors to engineering practitioners with between three and over 25 years of experience. The findings reveal participants' perspectives on SD, socializing forces, workplace writing, rhetoric, writing and thinking, and the value of writing. Participants identified few areas for course improvement and agreed that SD is generally effective in achieving its objectives. Participants also thought that writing played little to no role in facilitating the process of socialization into any given workplace; however, those asked indicated that the way engineers write reflects the degree to which they have been socialized into an organization. Further, participant statements about what constitutes effective workplace writing provide a portrait of disciplinary values and suggest diverse perspectives on the role writing plays in the workplace. On audience and persuasion, participant comments suggest a continuum of rhetorical awareness based on career experiences and organizational roles and reveal diverse perceptions concerning writer identity, the role of objectivity, and the roles of readers and writers. Also, participants were emphatic in accentuating the cognitive benefits of writing for engineers and also highlighted important differences between visual and textual thinking. Although participants recognized that writing facilitates thinking and career advancement, they also described several reasons for negative attitudes toward writing. Overall, these findings provide initial snapshots of diverse developmental stages at various junctures in an engineering career. This study has important implications for those involved with engineering education. Understanding engineering students' perceptions of writing in relation to the perceptions of more experienced engineering practitioners gives us a glimpse into how these engineers' conceptions about writing develop and change over time. Such awareness has implications for how educators can facilitate young engineers' growth via writing in the disciplines, metacognitive activities, and other means.
Keywords: composition; higher education